Effect Of Valuation Accuracy on Mortgage Valuation Performance in Kaduna Metropolis, Nigeria - Muhammad Hassan; Habu Mallam Baba; Isa Abdullahi (Zien Journals, 2021)
This study assessed the effect of valuation accuracy on mortgage valuation performance in Kaduna metropolis with a view to improving the quality of mortgage valuation practice. The study adopted a quantitative approach, where data was collected using questionnaires from 75 estate surveyors and valuers and 41 commercial Banks randomly selected from the study area. The instrument validity was established through scrutiny and evaluation by the research supervisor and experts in the study area, and reliability was determined via Cronbach’s alpha coefficient reliability test. The data collected was subjected to descriptive and inferential statistics to examine the degree of agreement and significance of the various variables. The study revealed that valuers adopt inappropriate method of valuation, lack access to adequate and reliable market data and respond to client’s influence. The study demonstrated that valuation accuracy has a positive and significant effect on mortgage valuation performance. It was recommended that emphasis should be placed on members’ specialization in the valuation practice, latest edition of Nigerian Institution of Estate Surveyors and Valuers’ valuations standards (2019) be widely distributed and enforced and Nigerian Institution of Estate Surveyors and Valuers should make it mandatory for all Estate Surveyors and valuers to submit relevant data (sales figures, rental values, outgoings, yield rates, etc) on all transactions with respect to property sales and lettings compulsorily for the purpose of building and regularly updating a data bank.
Keywords: Valuation; Accuracy; Mortgage; Performance